Plastic collapse of cylindrical shell-plate periodic honeycombs under uniaxial compression: experimental and numerical analyses. (June 2016) - Chen, Qiang; Shi, Quan; Signetti, Stefano; Sun, Fangfang; Li, Zhiyong; Zhu, Feipeng; He, Siyuan; Pugno, Nicola M.
Abstract: This paper studies the plastic collapse mechanisms of uniaxially-loaded cylindrical shell-plate periodic honeycombs with identical mass (or relative density) but varying geometric parameters, by series of in-plane and out-of-plane experiments and finite element numerical simulations. The coupled experimental-numerical results show that mechanical properties of the honeycomb can be optimized in all three loading cases, thanks to the complementary changes of the mechanical properties of cylindrical shell and plate as the geometric parameters vary. The work presents a concept to optimize lattice structures by combining different substructures, and can be used in designing new low-density honeycomb structures with desired mechanical requirements but less base materials and weight. Highlights: A cylindrical shell-plate assembled periodic honeycomb is presented. The mechanical properties of the honeycomb are optimized. The optimized mechanism is discussed. The structure could be used as a sandwich core materials.